Corporate Criminal Accountability: A Brief History and an Observation - Kathleen F. Brickey (Washington University Law Quarterly, 1982)
The pervasive influence enjoyed by large, publicly held corporations has inspired a body of scholarship that considers at length the need for effective mechanisms to regulate institutional behavior. Enforcement of penal statutes applicable to corporations is, of course, included among existing options, and renewed interest in criminally prosecuting corporations during the last decade has brought to the fore the true breadth of corporate exposure to criminal liability. While it has long been settled that corporations constitutionally may be held accountable for criminal misdeeds of their agents, one detects a current sense of uneasiness regarding the appropriate role and scope of corporate criminal liability. Have we, for instance, strayed too far from the mens rea model of criminality when dealing with institutional misbehavior? A vast array of penal statutes applicable to the corporate entity dispenses with any requirement of moral blameworthiness. Is it time, perhaps, to re-examine such offenses in light of traditional notions of culpability so that we may arrive at a "consensus" about what constitutes "truly culpable" corporate wrongdoing and eliminate criminal penalties for "trivial conduct?”
Keywords: Criminal liability